Criação e teste de uma escala para avaliação da estratégia de gestão do conhecimento : aplicação a um escritório de propriedade intelectual - Oliveira, Marcelo Fonte Boa (2004)
This dissertation aims at evaluating how the enterprises organize their strategies for the management of knowledge. Basically there are two strategic models presented in the literature: codification and personalization. However, there is an issue that is presented in the literature regarding the importance of prioritizing focus in only one of the mentioned strategic models. The main objective is to present a rank that is meant to analyze whether a leader enterprise in its segment has a strategic focus regarding the management ofknowledge. During the development of this work a theoretical reference will be followed in search of an explanation for the importance of the management of knowledge in the enterprises strategy. Points such as the characteristics of the Information Era and the basic concepts of the management of knowledge will be studied, comprising theoretical models that seek to explain how the knowledge is created and transferred within the enterprises. A model for measuring the strategic focus of an enterprise will be proposed. This model will be composed of structured indicators in form of a questionnaire. For every indicator there will be an evaluation scale and the questionnaire set will search the translation of the mentioned strategic focus. To sum up, the questionnaire will be tested in an Intellectual Property enterprise and statistic analyzes to evaluate it will be made. To achieve this goal the confirmatory factorial analysis procedure will be used. This model is a statistic tool that makes the evaluation of the analysis model as well as the structural model possible.